"Emad-Falih Transform" a new integral transform. Issue 8 (17th November 2021) - Kuffi, Emad; Maktoof, Sara Falih
Abstract: In this paper, a new integral transformation named "Emad-Falih Transform" has been proposed to solve linear ordinary differential equations with constant coefficients.